(untitled) (Research, Society and Development, 2021)
Healthy eating is responsible for providing us with health and a good quality of life. On the other hand, there are numerous diseases associated with poor diet and the rates are alarming, in addition to the issue of obesity, which is a major concern among adults and is increasingly common in children. The aim of this study was to evaluate the approach to food education in science textbooks of the eighth grade of elementary school, from schools in the municipality of Volta Redonda, Rio de Janeiro, Brazil. The study was developed from the analysis of the content of these books through a questionnaire prepared by the authors. After a qualitative analysis of the data, it became evident that the books in question cover most of the proposed content, however, it was not possible to point out the best or most complete. However, because they are different authors addressing the same subject, some themes are better emphasized in certain books and less in others.